Survey on metamaterial antennas. Issue 1 (February 2021) - Suganthi, J; Kavitha, T; Ravindra, V
Abstract: Metamaterials are popular in the antenna research area because of their unusual properties. Metamaterials can be used to surpass disadvantages of conventional microstrip antenna such as larger bandwidth, reduction in size of the antenna, better return loss and improvement in gain, directivity with acceptable amount of input power. The main aim of this paper to analyse the best model required to design a patch antenna with respect to the relevant application.